1994
DOI: 10.3354/meps112189
|View full text |Cite
|
Sign up to set email alerts
|

Drastic changes in otolith strontium/calcium ratios in leptocephali and glass eels of Japanese eel Anguilia /aponica

Abstract: Strontium (Sr) and calcium (Ca) contents and Sr/Ca ratios in otoliths of Japanese eel Anguilla japonica leptocephali and glass eels were examined. The Ca content was almost constant throughout the otoliths, except for the core, in which it was lower. Both Sr content and Sr/Ca ratios increased with age during the leptocephalus stage, but dramatically decreased at age 90 to 100 d. The otolith increment width also showed marked variation at ages 80 to 110 d, indicating the period of metamorphosis. These suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
89
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 14 publications
6
89
0
Order By: Relevance
“…Otake et al (1994) found an ontogenetic change in the Sr/Ca ratios in the otoliths of Anguilla japonica glass eels at the onset of metamorphosis that was indicated by an abrupt drop in the high Sr level maintained during the leptocephalus stage. Similar results were confirmed in tropical eels (A. celebesensis, A. marmorata, A. bicolor bicolor and A. bicolor pacifica: Arai et al 1999a,b) and other temperate eels in the southern hemisphere (A. australis: Arai et al 1999c;A.…”
Section: Introductionmentioning
confidence: 92%
“…Otake et al (1994) found an ontogenetic change in the Sr/Ca ratios in the otoliths of Anguilla japonica glass eels at the onset of metamorphosis that was indicated by an abrupt drop in the high Sr level maintained during the leptocephalus stage. Similar results were confirmed in tropical eels (A. celebesensis, A. marmorata, A. bicolor bicolor and A. bicolor pacifica: Arai et al 1999a,b) and other temperate eels in the southern hemisphere (A. australis: Arai et al 1999c;A.…”
Section: Introductionmentioning
confidence: 92%
“…(Otake et al 1994, Tzeng & Tsai 1994, Tzeng 1996, Tzeng et al 1997, 2000, in press, Secor 1999, Secor & Rooker 2000. The variability in migratory behaviours associated with habitat selection has recently been investigated for leptocephali metamorphosing to glass eels over the continental shelf (Cheng & Tzeng 1996, Wang & Tzeng 1998, 2000, Arai et al 2000, Shiao et al 2001) and for estuarine-and freshwater-resident yellow and silver eels (Tzeng et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The Sr/Ca ratios in the otoliths of Japanese eels Anguilla japonica drastically decrease when the eel larvae pass through a salinity gradient during migration from spawning ground to estuary while simultaneously transitioning from the leptocephalus to glass eel developmental stage (Tzeng & Tsai 1994). Otake et al (1994) suggested that this sharp decrease in Sr/Ca ratios marks the onset of metamorphosis. However, no direct evidence was given to validate this claim.…”
Section: Introductionmentioning
confidence: 99%